Analisis Kerusakan pada Permukaan Perkerasan Jalan Lingkar Kota Slawi Ruas Jalan Desa Kendalserut dengan Metode Bina Marga - Galang Hafiidh Bernanda; Wahudin Diantoro; Imron Imron (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
The Slawi city ring road is a road that connects several villages in the Tegal district, especially the Pangkah and Slawi sub-districts. This road is often passed by heavy vehicles such as trucks and other cars carrying goods, many motorized vehicles also pass on this road, especially students. With the volume of vehicles that are quite dense at certain hours and with minimal maintenance on road conditions, this causes a decrease in the quality of the road surface. With these problems, it is necessary to analyze the condition of road damage at STA 0+000 to STA 1+720. This study aims to determine the type and level of road damage using the Bina Marga 1990 method, determine the percentage value of each damage and calculate the priority order of the road as a reference for determining the repair program for the road. Data collection using the LHR survey is also needed to determine road condition values. Factors that cause road damage are the lack of routine maintenance on the road and the absence of drainage so that a lot of water stagnates during the rainy season which causes road damage to become more severe. The types of damage found on the Slawi City ring road are pothole damage, grain release, fatness and crocodile skin cracks.